Neighbourhood Abstraction in GROOVE - Rensink, Arend; Zambon, Eduardo (Electronic Communications of the EASST, 2011)
Important classes of graph grammars have infinite state spaces and therefore cannot be verified with traditional model checking techniques. One way to address this problem is to perform graph abstraction, which allows us to generate a finite abstract state space that over-approximates the original one. In previous work we developed the theory of neighbourhood abstraction. In this paper, we present the implementation of this theory in GROOVE and illustrate its use with a small grammar that models operations on a single-linked list.